Perception of Prosodic Division Depth in Spoken Poetry (A.S. Pushkin’s “Eugene Onegin”) - A. V. Kruglova (Научный диалог)
Pauses are one of the most universal markers of prosodic division in different languages. Their duration depends on various factors such as genre, syntax, and punctuation. In poetry, pauses not only help reveal the structure of the poem and emphasize its division into lines, but also reflect the varying degree of internal division within a line. This study presents the results of a perceptual experiment involving 11 participants who evaluated the presence and depth of prosodic breaks in spoken Russian poetry using a 5-point scale, which has been proven effective in previous experiments conducted on prose texts in Russian and Dutch. The experiment showed that native speakers successfully identify pauses in spoken poetry and consistently determine their depth. When evaluating the depth of division within a line, participants tended to use the lowest possible score. Additionally, a correlation was found between the duration of physical pauses in the speaker’s speech and the level of evaluation of prosodic breaks by the participants. These findings fill a gap in understanding the depth of prosodic division in poetry and confirm previously identified patterns of pause distribution in Russian poetry.